1962
DOI: 10.1002/lipi.19620640304
|View full text |Cite
|
Sign up to set email alerts
|

Autoxydations‐Versuche an Modellsubstanzen zur Frage der Fett‐Autoxydation

Abstract: Wenn man bedenkt, dai3 eine Nahrung rnit niedrigem Fettgehalt (2 Oio Schweineschmalz) und mit gleichen Teilen von Glucose und roher Reisstarke als Kohlenhydrat auch in einigen Hamstern Cholesterin-Gallensteine in 1 bis 2 Monaten hervorruft, ware es vielleicht angezeigt zu untersuchen, ob eine uber langere Zeit sich erstrekkende Ernahrung mit leichtverdaulichen Kohlenhydraten und u. U. ungenugendem Inhalt von ungesattigtem Fett eine der Ursachen der Cholesterin-Gallenstein-Bildung beim Menschen sein kann. Doch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1964
1964
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…CLXV With aqueous sodium chlorate in the presence of osmium tetroxide, /3-angelica lactone gives a mixture of 5-deoxy-DL-ribonic acid 7-lactone (CLXVI) and 5-deoxy-DL-lyxonic acid (CLXVII) (213). With aqueous hypobromous acid, /3-angelica lactone forms two di- The autoxidation of «-and /3-angelica lactones leads to the formation of hydroperoxides CLXX and CLXXI (280).…”
Section: Dimerization Of Butenolidesmentioning
confidence: 99%
“…CLXV With aqueous sodium chlorate in the presence of osmium tetroxide, /3-angelica lactone gives a mixture of 5-deoxy-DL-ribonic acid 7-lactone (CLXVI) and 5-deoxy-DL-lyxonic acid (CLXVII) (213). With aqueous hypobromous acid, /3-angelica lactone forms two di- The autoxidation of «-and /3-angelica lactones leads to the formation of hydroperoxides CLXX and CLXXI (280).…”
Section: Dimerization Of Butenolidesmentioning
confidence: 99%
“…Seyfarth and Schulz (3) and Rieche et al (4) studied the oxidation at 65 C of 2-and 3-butenoate esters, 0~-hydroxy butenoate esters, 3,6-heptadienoic acid esters, and the gamma lactones of 4-hydroxy-2-pentenoic and 4-hydroxy-3-pentenoic acids. Analysis of the peroxides formed showed that the position of hydroperoxide formation depends on factors which influence the activation of C-H groups (e.g., double bonds, ester, and hydroxyl groups).…”
Section: Introductionmentioning
confidence: 99%